The effect of social entrepreneurial behaviour towards organizational performance: A study on Bumiputera entrepreneurs in Malaysia - Rahim, Hardy Loh; Mohtar, Shahimi; Ramli, Azahari (International Academic Research Journal, 2015)
It has long been acknowledged that SMEs contribute significantly to overall economic performance in Malaysia. However, the performance of SMEs still has not reached the stage of full potential. Although the number of SMEs hit more than 90% of the total establishments in most countries, including Malaysia, it does not show the strength of a company or industry.Furthermore, as the biggest ethnicity in Malaysia, the growth in Bumiputera entrepreneurial activity has not been in tandem with the pace of the overall development of the nation.Thus a transformation is needed for them to develop their organizational resources and capabilities that will move them to become more competitive.Meanwhile, social entrepreneurship is becoming a movement in Malaysia.The awareness and acceptance of social entrepreneurship is picking up its pace in the country.The ministers of Malaysia has urged for social entrepreneurship within the organizations and academicians has suggested that social entrepreneurial behaviour of an entrepreneur could contribute to organizational performance.Therefore this study aims to examine the effect of social entrepreneurial behaviour towards organizational performance of Bumiputera SME owners in Malaysia.This research employs quantitative analysis with 384 respondents participated in this study by implementing the systematic random sampling technique from a total of 645,136 SME owners in Malaysia.The result shows that social entrepreneurial behaviour had positive effect towards organizational performance.